A traditional bungalow in Mazagaon Koliwada - Mumbai Archive Project Team (Jio Institute, 2024)
Bungalows at Mazagon Koliwada have traditional architecture. They are usually one or two stories high, with protruding balconies held up by wooden brackets. Tiled roofs drain rainwater during the monsoon season. The interiors are flooded with natural light and fresh air thanks to the open balconies. The building entry opens onto the street, and the upper levels are connected by a wooden staircase.